Rainproof film covering method for solid waste landfill area - ZHU MI; WU FEI; CHEN XIANG; WANG SHUANGCHUN; SUN WEIGUO; ZHANG XUN (2018)
The invention relates to a rainproof film covering method for solid waste landfill area. The rainproof film covering method adopts multi-layer film composite covering, the fixation effect is good, therainproof effect is good, and the rainproof film is not prone to being damaged. The rainproof film with suitable size and composition is replaced in time according to season and month so as to ensurethat the leachate content does not exceed the standard. 本发明涉及种用于固体废物填埋区域的防雨膜覆盖方法，采用多层膜复合覆盖，固定效果好，防雨效果佳，不易损坏，且根据季节及月份及时更换适合尺寸及组份的防雨膜从而保证渗滤液含量不超标。